Blots and brains. A note on the centenary of Hermann Rorschach's death. (December 2022) - Brugger, Peter
Abstract: This historical note is a commemorial of Rorschach, the person, and Rorschach the test. Hermann Rorschach died 100 years ago, not quite a year after the publication of his book containing the 10 inkblots. These have reached an iconic status, but the "Rorschach Test" as used in psychiatry, legal organizations and aptitude assessments is not quite what Hermann Rorschach designed it for in the first line. A first section of this article introduces Hermann Rorschach as a man with very broad interests and an inclination to ask cognitive science questions that are still challenging today. A second section provides a critical summary of the fate of the ten inkblots after Rorschach's death - how they conquered the whole world in a time with a pronouced "psychometric attitude", and also how they failed in some attempts to measure personality traits in special populations. A final section focuses on recent research on one particular aspect of a testee's associations to the inkblots: "movement responses", i.e. the perception of implied motion. Here, neural and behavioral correlates have been demonstrated by modern neuroimaging techniques. One study, which set out to validate both the Rorschach as a personality test and the view that the two cerebral hemispheres correspond to divergent "personalities" is also summarized. The viewpoint concludes by suggesting that future work with inkblots should consider Rorschach's original intention to use inkblots to uncover basic laws of perception. Modern applications of computer-generated pseudorandom stimuli (random dot arrays or stochastic noise) would have been embraced by Hermann Rorschach as he appreciated the impact of visual noise for the study of vision and visual cognition.